Prospects for global food security: a critical appraisal of past projections and predictions - McCalla, Alex F.; Revoredo, Cesar L. (International Food Policy Research Institute, 2001)
During the last half century, a number of individuals and institutions, including the Food and Agriculture Organization of the United Nations (FAO) and IFPRI, have engaged in projections of future food demand, supply, and related variables. In this brief, Alex McCalla and Cesar Revoredo compare projections with real-life outcomes. Projections forecast outcomes on the basis of certain underlying factors. If such forecasted outcomes are undesirable, changes may be made in the underlying factors so that the projections may not, in fact, come to pass. Many projections serve this precise goal. Therefore, the success of projections may not be that they match actual outcomes but that they avoid such outcomes by promoting action to change underlying variables. Unlike predictions, which are successful only if they match actual outcomes, projections that differ from actual outcomes may reflect either poor projection models or changes in underlying variables, possibly caused by the projections themselves.